Effects of contraception methods on female sexual function and quality of life - Gürbüz, Tuğba; Dokuzeylül Güngör, Nur; Tanrıdan Okçu, Nefise; Yurci, Arzu (Journal of Surgery and Medicine, 2020)
Aim: Many women of reproductive age who use contraceptive methods have sexual dysfunction and reduced quality of life. This study aimed to evaluate the effects of various contraceptive methods on female sexual function index (FSFI) and quality of life scale (SF-12). Methods: This prospective observational study was conducted on the patients admitted to the Gynecology and Obstetrics outpatient clinic between August and October 2020. FSFI total score and FSFI sub-domains (desire, arousal, lubrication, orgasm, satisfaction, and pain) and SF- 12 were used to compare the differences between the groups using various contraceptive methods (Mirena, Copper RIA, tubal ligation, condom, and oral contraceptive pill). The demographic characteristics of the patients, the FSFI, and SF-12 data were collected by the researchers face to face. Results: A total of 228 subjects with a mean age of 30.32 years participated in the study. FSFI scores of the patients using and not using contraceptive methods were significantly different (P<0.001), while PCS-12 (P=0.122) and MCS-12 (P=0.122) scores were similar. The mean total FSFI score was 23.36. Conclusion: The study concluded that women using contraceptive methods had lower total FSFI scores than those who did not, and statistically significant differences were found between the two groups in terms of lubrication, desire, and pain subdomains. We found that contraception methods significantly affected the sexual function of women, but not their quality of life.